2021
DOI: 10.1161/circresaha.120.316966
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Congenital Heart Disease Caused by NAA15 Haploinsufficiency

Abstract: Rationale: NAA15 is a component of the N-terminal (Nt) acetyltransferase complex, NatA. The mechanism by which NAA15 haploinsufficiency causes congenital heart disease (CHD) remains unknown. To better understand molecular processes by which NAA15 haploinsufficiency perturbs cardiac development, we introduced NAA15 variants into human induced pluripotent stem cells (iPSCs) and assessed the consequences of these mutations on RNA and protein expression. Objective: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 75 publications
6
42
2
Order By: Relevance
“…In line with previous reports [ 21 , 27 , 37 ], and as evidenced from protein expression levels when probing for the NatA subunits by means of Western blotting, exclusive knockdown of NAA10 also results in a significant destabilization of NAA15 ( Figure S1 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous reports [ 21 , 27 , 37 ], and as evidenced from protein expression levels when probing for the NatA subunits by means of Western blotting, exclusive knockdown of NAA10 also results in a significant destabilization of NAA15 ( Figure S1 ).…”
Section: Resultssupporting
confidence: 92%
“…By making use of CRISPR/Cas9 gene editing, NAA15 haplo-insufficient and deficient induced human pluripotent stem cells (iPSCs) could successfully be obtained. Interestingly, in these iPSCs, a mere partial effect on NatA-dependent NTA acetylation was observed [ 37 ]. In case of NAA15 deficiency and since a role for NAA16-NAA10 complexes has been proposed to act as a potential backup system for the NAA15-NAA10 NatA complex [ 38 ], akin NAA11 expression, expression of its homologue NAA16 in human cells may also (in part) be responsible for this observation.…”
Section: Introductionmentioning
confidence: 99%
“…Although this was not a significant result statistically (p=0.09), it is worth noting that peptidyl-prolyl cis-trans isomerase A (PPIA), having a 10.3% decrease in amino-terminal acetylation, was previously identified with decreased amino-terminal acetylation in patient-derived B cells and fibroblasts in boys with the S37P mutation in NAA10 [25], along with being decreased in siNatA knockdown HeLa cells [1]. PPIA also had decreased amino-terminal acetylation in one sample from homozygous null NAA15 L314*/L314* induced pluripotent stem cells [47].…”
Section: Naa10-deficient Mice Have a Functionally Active Nata Complexmentioning
confidence: 93%
“…A recent study demonstrated how the haploinsufficiency of NAA15 , a known CHD gene, perturbs cellular function in hiPS-CMs. Heterozygous loss of function, compound heterozygous, and missense NAA15 variants were introduced into hiPSCs using CRISPR/Cas9 gene editing, and the consequences of these mutations on hiPS-CM phenotype and RNA and protein expression were assessed [ 82 ]. The study identified four CHD-causing genes ( DHCR7 , MAP2K2 , NSD1 , and RPL5 ) that were differentially expressed in NAA15 haploinsufficiency, providing molecular-level mechanisms behind the pathogenicity.…”
Section: Human Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…The study identified four CHD-causing genes ( DHCR7 , MAP2K2 , NSD1 , and RPL5 ) that were differentially expressed in NAA15 haploinsufficiency, providing molecular-level mechanisms behind the pathogenicity. Importantly, the study provided a reference on how to estimate the pathogenicity of NAA15 variants of uncertain significance in patient-derived cells [ 82 ].…”
Section: Human Induced Pluripotent Stem Cellsmentioning
confidence: 99%